PENGARUH HUTANG LANCAR DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB. SEKTOR FARMASI DI BURSA EFEK INDONESIA - Yancik Syafitri; Firdaus Sianipar (Universitas Tridinanti, 2022)
This research basically examines the effect of current liabilities and accounts receivable turnover on the profitability of pharmaceutical sub-sector companies listed on the Indonesian stock exchange. The purpose of this study was to determine the effect of current liabilities and accounts receivable turnover both simultaneously and partially on profitability (Return On Assets) in Pharmaceutical Sub Sector Companies listed on the Indonesian stock exchange. The sample in this study is the financial report data of pharmaceutical sub-sector companies for 5 periods. This study uses multiple linear regression analysis. The results of data processing in obtaining the coefficient of determination (R square) R is 0.115, meaning that current liabilities and accounts receivable turnover contribute to influencing profit or profits of 11.5% while the remaining 88.5% is the influence of other variables that are not present in this study. Current liabilities and accounts receivable turnover simultaneously have a significant effect on profitability together. This can be seen from the results of the f count of 7,924 and the f table value of 3.19 with a sig. 0.001 or f count > f table (7.924 > 3.19). Current liabilities partially have a significant effect on profitability (ROA) with a sig. 0.019 which means it is smaller than 0.05 or 0.019 <0.05 and the value of t count is 2.424 which is greater than t table 2.01063, t count > t table (2.424> 2.01063). Receivables turnover partially does not have a significant effect on profitability (ROA) with a sig. 0.512 which means greater than 0.05 or 0.512> 0.05 and the value of t count 0.661 is greater than t table , t count > t table (0.661> 2.01063).Keywords: Current Debt, Accounts Receivable Turnover, Profitability